Cytogenetic features in primary myelodysplastic syndrome Egyptian patients - Elnahass, Yasser (J Adv Res, 2018)
Karyotype is the most important diagnostic and prognostic parameter in myelodysplastic syndromes (MDS) and is abnormal in approximately 50% of patients. We emphasized the importance of chromosomal analysis and reported the most frequent cytogenetic abnormalities in 50 MDS (29 males (58%) and 21 females (42%), median age: 57.5 years) Egyptian patients using conventional banding analysis (CBA). Karyotype description was conducted according to the International System for Human Cytogenetic Nomenclature (ISCN, 2013). Patients were diagnosed based on complete history, bone marrow (BM) aspirate, peripheral blood (PBL) examination, and Iron stain. MDS with multilineage dysplasia (MDS-MLD) was the most frequently encountered subtype; 19/50 (38%) followed by MDS with single lineage dysplasia (MDS-SLD); 11/50 (22%). 27/50 patients (54%) showed a normal karyotype while 23 patients (46%) showed clonal nonrandom chromosomal abnormalities. Most patients with MDS with excess blasts-II (MDS-EB-II) showed abnormal karyotype (3/4; 75%) followed by MDS-EB-I (3/5, 60%) and MDS-MLD (10/19, 53%). Among 50 primary MDS patients; 14/50 (28%) had a single chromosomal abnormality, 3/50 (6%) had double chromosomal abnormality, and 6/50 (12%) had complex karyotype. Male sex was more frequently associated with higher IPSS prognostic risk categories than female gender. The most common single chromosomal abnormalities were −5/del5q; 7/50 (14%) patients followed by −7; 4/50 (8%) patients. +8, del20q and delY were each detected in 1/50 patient (2%). Abnormalities of chromosome 5 (−5/del5q) as a single chromosomal abnormality was the most frequent chromosomal abnormality among Egyptian primary MDS patients followed by complex karyotype. Cytogenetic characteristics of MDS Egyptian patients were similar to North African and European patients. Karyotype offers useful information in establishing accurate diagnosis and male gender is an important predisposing factor that can predict worse prognosis in MDS patients.